Adoption attitude towards the usage of pusher box technology in the rubber industry - Jabar, Juhaini; Abdul Karim, Mohd Haradzi; Mohd. Yusof, Sitinor Wardatulaina; Murad, Murzidah Ahmad; Abdul Khalid, Fararishah (Advances in Social Sciences Research Journal, 2017)
This study has investigated the relationship between the adoption attitude towards usage of automatic pusher box system in rubber plant industry. The study was conducted in a rubber factory under Felda Global Venture (FGV) which is located in Negeri Sembilan, Malaysia. This company strive to be the global leader in natural rubber processing offering high quality products and services through good manufacturing and eco-friendly practice. Therefore, automatic pusher box system is one of the new technologies that is used in the company. Furthermore, this automatic pusher box it is suitable for saving manual labor hours and labor costs by replacing the current semi-automated system.